The Nexus Between Infrastructure and Export: An Empirical Evidence from Pakistan. (May 2020) - Rehman, Faheem Ur; Ding, Yibing; Noman, Abul Ala; Khan, Muhammad Asif
This research, by using the autoregressive distributive lag method, examines the long- and short-term causal relationship between infrastructure and exports in Pakistan over the period 1990–2017. The empirical results revealed the existence of short- and long-term bi-directional causality concerning infrastructure and export in Pakistan. The results demonstrated that infrastructure strongly improves export in the short and long run. Conversely, export encourages the quality and availability of infrastructure in Pakistan in the long run. Furthermore, this study also uses sub-indices of infrastructure individually as dependent and independent variables. The study result demonstrated that the long- and short-term effects of infrastructure and its sub-indices (transport, electricity, communication, finance) on export is positive and significant. Also, when infrastructure sub-indices are used as dependent variables, the results indicate that the effect of export on sub-indices is positive and significant in the long run; however, in the short run, it is insignificant. The bi-directional linkage between infrastructure and export suggests that improving the quality and increasing the availability of infrastructure would enable Pakistan's economy to catch up with the advanced economies, specifically in export. Furthermore, control variables of per-capita GDP, exchange rates, human capital, and domestic spending also expand the bi-directional causal relationship between Pakistan's infrastructure and exports.